Evaluation of a hand hygiene campaign in outpatient healthcare clinics - Kaur, Ramandeep (Kansas State University, 2012)
Hand hygiene by healthcare workers is an effective means of preventing healthcare-acquired infections. However, hand hygiene compliance can be low among healthcare workers. This study used introduction of a gel sanitizer and informational poster as interventional tools in attempt to improve hand hygiene in two outpatient healthcare clinics. Healthcare workers at two outpatient clinics were observed for frequency of hand hygiene (attempts vs. opportunities). Gel sanitizer and informational posters were introduced together as an intervention. Direct observation of hand hygiene frequency was performed during baseline, intervention, and follow-up. A post-study survey of healthcare workers was collected. In both clinics, baseline hand hygiene was poor (11% and 21%) but significantly improved (p[less than or equal to]0.0001) after interventions (36 and 54%), and was maintained (p>0.05) through the follow-up period (32 and 51%). Throughout the study, post-contact hygiene was statistically observed more than pre-contact hygiene. In both clinics, healthcare workers self-reported a preference for soap and water, yet observations showed that sanitizer use predominated over soap and water use when sanitizer was available after the intervention. Fifty per cent of the surveyed healthcare workers considered the introduction of gel sanitizer to be an effective motivating tool for improving hand hygiene. Hand hygiene performance by healthcare workers in outpatient clinics may benefit from promoting gel sanitizer and using informational posters. Direct observation by trained observers may provide more accurate information of hand hygiene tool preference compared with survey results.
Keywords: Hand hygiene; Outpatient clinics; Handwashing; Gel sanitizer; Posters; Public Health (0573)